Children and Young People (Scotland) Act: reflections on the passage of the act - Marie McCormack (Scottish Journal of Residential Child Care)
The Children and Young People (Scotland) Act was passed by the Scottish Parliament on 19th February 2014 and received Royal Assent on March 27th 2014. It has been an interesting journey and not without its challenges. This article provides an overview of the Bill's progress through Parliament, details the Act's provisions, with particular attention given to the measures affecting looked after children and care leavers, and provides some reflections on the process.